Lupus Nephritis and Pregnancy: Case Report - Ahmet Kale; Ali İrfan Güzel; Mahmut Erdemoğlu; Umur Kuyumcuoğlu; Nurten Akdeniz; Kadir Kangal (Medical Network, 2009)
Our aim is to report of a pregnant woman with lupus nephritis; A 33-year-old multigravida (gravida:5,parity: 4) with an intrauterine pregnancy at 34 weeks of pregnant woman with 5 years of uncontrolled SLE. Pregnancy can be successful in most women with lupus nephritis. Pregnancy in SLE should be planned and a management strategy should be agreed in full consultation with the patient, prior to conception. Women with SLE frequently need treatment throughout pregnancy. It is essential that the maternal disease is well controlled prior to, during and after pregnancy to ensure the best possible outcome for the mother and child.